Exploring Test Concept and Measurement Through Validity and Reliability Process in TVET Research: Guideline for The Novice Researcher - Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Gloeckner, Gene (Journal of Technical Education and Training, 2023)
Validity and reliability are important aspects of research, especially in social science and TVET research. The scales used in research that are important factors to enable good research results. The objective of this paper is to provide insight into important concepts of validity and reliability and also to introduce the major methods to assess validity and reliability as they relate to social science and TVET research. The research design and approach used for this study was a non-experimental research design. The data are using retrospective data and descriptive statistics which were used to run the simulation and analysis. The outcome of this research suggests that Cronbach’s Alpha is the best method to use when checking the reliability in terms of internal consistency. The alpha provides various information that can benefit the researcher, especially in novice research, The result from the simulation shows the importance of conducting validity and reliability test during the research process. It not only provided evidence but also confidence because it reflected consistency and accuracy.